2011
DOI: 10.1161/circinterventions.111.961847
|View full text |Cite
|
Sign up to set email alerts
|

Further Ex Vivo Evidence Supporting Higher Aspirin Dosing in Patients With Coronary Artery Disease and Diabetes

Abstract: A spirin remains the cornerstone antiplatelet agent for primary and secondary prevention in patients with diabetes mellitus (DM), a disease associated with heightened platelet reactivity, endothelial dysfunction, and inflammation. 1,2 Patients with DM are at a greater risk of death, myocardial infarction, and stroke resulting from thrombotic event occurrence than are patients without diabetes. Because reactive platelets play a central role in the genesis of thrombotic events, the antiplatelet effects of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Clinical trial data have supported that the most optimal dose for patients with known coronary artery disease when weighing risks and benefits is between 75 and 100 mg [46]. The ASPECT clinical trial [23,47], the largest serial pharmacodynamic investigation of dose-dependent effects of aspirin on platelet aggregation in individuals with known coronary artery disease, has shown that aspirin effects on arachidonic acid-induced platelet aggregation are an important means of determining aspirin insensitivity in those with known coronary artery disease, but that ADP- and collagen-induced aggregation are also potentially important factors in determining whether aspirin is exerting its antiplatelet effects. Our data regarding effects of ADP and collagen at low dose on aggregation suggest that it may be that aspirin + fish oil exert a greater effect than aspirin alone 4 hours after ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial data have supported that the most optimal dose for patients with known coronary artery disease when weighing risks and benefits is between 75 and 100 mg [46]. The ASPECT clinical trial [23,47], the largest serial pharmacodynamic investigation of dose-dependent effects of aspirin on platelet aggregation in individuals with known coronary artery disease, has shown that aspirin effects on arachidonic acid-induced platelet aggregation are an important means of determining aspirin insensitivity in those with known coronary artery disease, but that ADP- and collagen-induced aggregation are also potentially important factors in determining whether aspirin is exerting its antiplatelet effects. Our data regarding effects of ADP and collagen at low dose on aggregation suggest that it may be that aspirin + fish oil exert a greater effect than aspirin alone 4 hours after ingestion.…”
Section: Discussionmentioning
confidence: 99%